Odbiorca przewidywany w powieści Sny i kamienie Magdaleny Tulli w oryginale i przekładzie Jany Unuk na język słoweński - Gruda, Marlena (Przekłady Literatur Słowiańskich, 2015)
The designated reader in the romance novel Dreams and stones by Magdalena Tulli, in the original and the translation by Jana Unuk into Slovenian The designated reader of the original Sny i kamienie by Magdalena Tulli and the designated reader of the translation Sanje in kamni by Jana Unuk are two separate subjects. The reason for the difference is the differing configuration of the relationships between the current narrator, intersemiotics and the pragmatism of the translation as well as the differing functions in each of these texts’ socially‑cultural reality. A translator, who is first a reader of the original, and then the author of the translation, exercises a double actualization on the basis of her/his own behavior, life experiences and potential experiences as a reader of the text. The translator’s way of reading and her interpretation, which is focused on the historical context, is especially noticeable in the lexical (the translation of collocations, idioms and metaphors) and grammatical level, modal structure, determination of categories of time, axiological categories of „the absolute” and metalinguistics. The work Dreams and Stones by Magdalena Tulli is, due to the plethora of philosophical and historical contexts, its structural composition and multifacetedness the cause of multiple meanings of interpretation and therefore, contains multiple possible translation solutions. Key words: reader, city, interpretation, idiom, context, perspective